Collaborative relaying strategies in autonomic management of mobile robotics - Barraca, João Paulo
Mobile robotics is a field that presents a surprising set of challenges to communications. One concept that can result in radically different solutions in mobile robotics is that of collaborative and cooperative communications. Cooperative techniques in wireless networks can enhance the performance of communication especially in cases where a small number of robots can be used to aid the establishment of reliable and efficient communication links. In this paper, we present a scenario for hybrid mobile robotics, where a small number of carriers are able to reposition nodes according to communication needs. We developed a common information management layer in order to coordinate cooperation (including communication aspects) between all units (information nodes and robots) according to high level self-established policies. We select IEEE 802.11 technology as the technology for the communication infrastructure and explore its potential for cooperative mobile environments in terms of power and spectrum efficiency presenting the rules required to reconfigure such a mobile robotic environment.